Catalytic Formation of Monosaccharides: From the Formose Reaction towards Selective Synthesis. Issue 7 (16th June 2014) - Delidovich, Irina V.; Simonov, Alexandr N.; Taran, Oxana P.; Parmon, Valentin N.
Abstract The formose reaction (FR) has been long the focus of intensive investigations as a simple method for synthesis of complex biologically important monosaccharides and other sugar‐like molecules from the simplest organic substrate—formaldehyde. The fundamental importance of the FR is predominantly connected with the ascertainment of plausible scenarios of chemical evolution which could have occurred on the prebiotic Earth to produce the very first molecules of carbohydrates, amino‐ and nucleic acids, as well as other vitally important substances. The practical importance of studies on the FR is the elaboration of catalytic methods for the synthesis of rare and non‐natural monosaccharides and polyols. This Minireview considers the FR from the point of view of chemists working in the field of catalysis with emphasis on the mechanisms of numerous parallel and consequent catalytic transformations that take place during the FR. Based on its kinetics, the FR may be considered as a non‐radical chain process with degenerate branching. The Minireview also considers different approaches to the control of selectivity of carbohydrate synthesis from formaldehyde and lower monosaccharides.